National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 5 major local authorities, the county and county borough councils. They will stand in their ordinary constitutional relationship with the central Ministry, but their general arrangements for these local services are made subject to the Minister's approval. (c) For the personal practitioner services both in the Health Centres and outside — i.e. the family doctor and dentist and the pharmacist — new local executive machinery is created, in the form of local Executive Councils. One half of the members of each of these Councils will consist of people nominated by the major local authorities and by the Minister, and the other half of people nominated by the local professional practitioners concerned. There will normally be an Executive Council for each of the major local authorities' areas, and they will work within national regulations made by the Minister. 10. By the Minister's side, to provide him with professional and technical guidance, there is to be set up a Central Health Services Council. This will include people chosen from all the main fields of experience within the service — with various standing committees of experts on particular subjects, medical, dental, nursing and others. 11. Each of these branches of the new organisation is described in more detail in the rest of this paper. HOSPITAL AND SPECIALIST SERVICE 12. This part of the service covers hospital and consultant services of all kinds, including general and special hospitals, maternity accommodation, tuberculosis sanatoria, infectious diseases units, provision for the chronic sick, mental hospitals and mental deficiency institutions, accommodation for convalescent treatment and medical rehabilitation, and all forms of specialised treatment— e.g. orthopaedics, cancer, neuro-surgery, plastic surgery, paediatrics, gynaecology, ophthalmic services, ear, nose and throat treatment, and others. 13. It is made the Minister's general duty to provide these physical and mental hospital services but he is to entrust their administration to Regional Hospital Boards, together with separate Boards of Governors for the teaching hospitals, in manner to be described later. 14. The existing premises and equipment of voluntary and public hospitals are transferred to the Minister under the Bill, and he is empowered also to acquire by purchase — if necessary — other hospitals and their equipment which may be required for the purposes of the new service. If in any particular case he is satisfied that the transfer of a hospital is not in fact necessary for the new service he can — with that institution's concurrence — except it from transfer. The general transfer of hospitals includes the present mental hospitals and mental deficiency institutions. 15. The endowments of voluntary teaching hospitals — defined in the Bill to mean, broadly, all their property other than buildings and their contents — will pass, not to the Minister, but directly to the new Boards of Governors, who are to be free to use them as they think best but are required, so far as practicable, to see that the purposes for which they were previously usable are still observed. 16. The endowments of other voluntary hospitals are to pass to a new Hospital Endowment Fund which the Minister is to set up and administer in the following way. He is first to meet from the Fund, to such extent as may 292/847/4/115